Environment and social justice an international perspective - Taylor, Dorceta E. (Research in social problems and public policy ;, 2010)
This volume examines domestic and international environmental issues from an environmental justice perspective. The book is a compilation of original research articles and is divided into six parts. Articles in Part I focus on urban environmental issues and sustainability including Central Park's influence on historical and contemporary models of funding public parks, London's community-based efforts to deliver affordable fresh food to the poor and the relationship between sustainable living, green consumption and social justice concerns in an ecovillage in New York. Part II concentrates on water resources and the hazards of toxic fish consumption. Part III features food security, agriculture and land loss. Energy and the theme of land and resource loss in host communities is the focus in Part IV. It discusses the poverty that is pervasive in communities hosting extractive oil and gas installations and the industry and attitudes towards it in rural Trinidad and Nigeria. Part V employs spatial analyses techniques to examine siting and toxic releases and Part VI examines diversity and environmental attitudes and presents findings of national studies and environmental conflicts.